Echoing Syari'ah in City Spaces: The Framing Process and Political Mobilization of the Islamic Movement in North Sumatra - Faisal Riza (Ulumuna, 2023)
This article discusses the Islamic political movement in fighting for sharia as an ethic of life in urban areas in Indonesia. In a more detailed manner, this article explores the idea of sharia as the main ingredient in the framing process and explores the movement's strategy to resonate with this frame, which then opens up opportunities for the formation of a wave of support for serial movement actions in Medan, North Sumatra. With the framing model in social movement studies, the data was collected from observations and interviews with several movement actors, and several supporting documents. This study found that the idea of this movements such as “Negara Kesatuan Republik Indonesia Bersyari’ah” (Indonesia Nation State based on Sharia) which is close to the social psychology of the masses met with the right events to generate great support for the movement. The ability of the elites to concoct the movement ideas, and the management of social media to spread such framing, made a mass wave of supporters strengthen. The struggle for sharia in the public space played by the movement here basically does not have a clear political agenda unless, temporarily, it is used only in electoral momentum, resonating as an expressive channel of the defeat against other groups in controlling the city's political economy space. Here, I argue that the study of ideology in social movements requires an expansion of dimensions that can explain more fully why a movement immediately grows or shrinks briefly or lasts a long time.